Dissemination of information : an examination guide book - Wilson, Thomas D.; Stephenson, James (Londonv : Clive Bingley, 1965)
This volume examines the dissemination of information with specific focus on special libraries. Topics include: special libraries; source of information; methods of dissemination; library publications; copyright; language barrier; abstracts and abstracting; finding and meeting users needs; theory of information retrieval; indexing in special libraries and mechanical and electronic methods.
Includes index.
lje 21/01/2019
Loans
Keywords: Special libraries; Information services; Information storage and retrieval systems